Intracholecystic Papillary Neoplasm: A Recently Described Rare Entity - Gupta , Vertika (Research Highlights in Disease and Health Research Vol. 6, 2023)
Intracholecystic papillary neoplasm (ICPN) is a rare, polypoidal, mucosal neoplasm that forms an intraluminal mass and measures \(\ge\)1 cm in size. It is usually non-invasive but may show low-grade or high-grade dysplasia. It shows a female predilection. Pain in the upper outer quadrant of the abdomen is the most common symptom. Pathologically it is believed to represent an “adenoma-carcinoma” sequence. Grossly, the intraluminal, papillary growth may be sessile or pedunculated and exhibits a size range of 1.0- 8.0 cm. It usually occurs in the body and fundus of the gall bladder. Microscopically, there is proliferation of glands arranged back-to-back with a scant amount of intervening stroma. These glands grow in papillary, tubular, or mixed tubulopapillary patterns. Morphologically, they exhibit various lineages which include gastric, biliary, oncocytic, and intestinal subtypes each having a specific immune profile. They have a better prognosis as compared to other bile duct and pancreatic malignancies. As it is a recently described entity, the features of ICPN are not clearly defined.